A Cognitive Assessment Instrument for HOTS Development in Technical Drawing Subjects Utilizing Quizziz Learning Platform - Widiyanti, Widiyanti; Dianawati, Roswina; Futachi, A.S. (Jurnal Ilmu Pendidikan, 2023)
Assessment or evaluation is the activity of collecting student information or a program of activities related to certain dimensions or attributes, such as student learning outcomes in teaching a field of study or the effectiveness of studying a field of study organized by the teacher, to be compared. Dimensional or characteristic excellence standards are associated with students or activity programs. For example, Quizizz, a digital platform that helps students master reading, is a multiplayer class activity that allows all students to practice reading skills using mobile devices, such as tablets, iPads, and Smartphones. This research use the Research and Development (R&D) method using the ADDIE research development model which is very applicable in the development of formal education. Based on the results of the validation value analysis carried out by two validators, the average percentage of very feasible category assessment instruments was 90.62 percent. Based on the results of the validity test shown on the 32 multiple choice HOTS questions used in the pilot study with 33 students, 26 items were determined to be valid. Based on the results of the reliability test, the value of the test analysis is included in the "high" category. The study of the difficulty level of the 32 questions yielded the following results: 15 simple questions, 14 moderate questions, and three challenging questions. In addition, according to the analysis of discriminatory power, nine items fall into the proper category, 21 items fall into the good category, one item falls into the poor category, and one item falls into the very poor category.